2021
DOI: 10.7717/peerj.11952
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of one of the most endangered freshwater fish species in Mexico:Tlaloc hildebrandi(Miller, 1950) and recognition of its evolutionarily significant units

Abstract: The endangered Chiapas killifish Tlaloc hildebrandi is an endemic freshwater species that lives in four subbasins of the Grijalva and Usumacinta basins, and one of the most geographically restricted species of the Produndulidae family. The species was originally described as endemic to springs in the high limestone plateau in San Cristóbal de Las Casas in the Río Amarillo subbasin (upper Grijalva basin). However, it was recently recorded in the Jataté and Tzaconejá subbasins in the upper Usumacinta basin, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Tlaloc hildebrandi inhabits the Fogotico River and its tributaries and in the upper reaches of the Grijalva-Usumacinta system, in Chiapas, México (Beltrán-López et al, 2021;Domínguez-Cisneros et al, 2017;Velázquez-Velázquez & Schmitter-Soto, 2004). It exhibits a restricted extent of occurrence, because the number of locations where this species occurs is limited to three, based on the recognition of at least three evolutionarily significant units (Beltrán-López et al, 2021;Velázquez-Velázquez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tlaloc hildebrandi inhabits the Fogotico River and its tributaries and in the upper reaches of the Grijalva-Usumacinta system, in Chiapas, México (Beltrán-López et al, 2021;Domínguez-Cisneros et al, 2017;Velázquez-Velázquez & Schmitter-Soto, 2004). It exhibits a restricted extent of occurrence, because the number of locations where this species occurs is limited to three, based on the recognition of at least three evolutionarily significant units (Beltrán-López et al, 2021;Velázquez-Velázquez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the structure of the community in the upper regions of these rivers notably differs (Gómez-González et al 2015;Velázquez-Velázquez et al 2016;Soria-Barreto et al 2018). Studies of systematic, biogeography and population genetics have revealed that the upper regions of the two basins have independent evolutionary histories (Elías et al 2021;Beltrán-López et al 2021;Terán-Martínez et al 2021). The presence of relic endemic species such as the catfish of Chiapas (Lacantunia enigmatica Rodiles-Hernández, Hendrickson et Lundberg, 2005) and the livebearer (Xenodexia ctenolepis Hubbs, 1950) of the upper Usumacinta are evidence of the region's unique biogeographic history (Rodiles-Hernández et al 2005;Hrbek et al 2007;Elías et al 2021).…”
Section: Introductionmentioning
confidence: 99%